Modelling the green transition of the Chinese economy - David An (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
This paper develops a stock-flow consistent (SFC) macroeconomic model with an energy sector for China to investigate the effect of green policies on green transition and the economy. We provide an analytical solution for green transition that illustrates the relative cost of using conventional energy with respect to renewable energy to determine the share of renewable energy and how the development of the energy sector promotes green transition. Our solution also demonstrates the necessity of green policies for a green transition. We calibrate the model to the national determined contributions (NDCs) scenarios from the Network for Greening the Financial System (NGFS) and run simulations from 2019 to 2035. The results show carbon taxes stimulate green transition but have a negative impact on the economy, accompanied by a reduction in economic growth, current account deficit and a rise in inflation. Carbon taxes deteriorate firms' balance sheets. Governments benefit from carbon taxes in the short run but face a higher public debt to GDP ratio in the long run. Carbon taxes reduce carbon intensity and carbon emissions. We also compared the effect of green fiscal policy to conventional fiscal policies financed by carbon taxes (carbon rebate). Green subsidies benefit economic growth more effectively. They reduce inflation caused by carbon taxes and stimulate the green transition further.
Keywords: E12; F41; Q41; Q42; Q58; 330; Stock-flow consistent modelling; Open economy; Energy pricing; Renewable energy; Climate policy